Positive Status of Epstein-Barr Virus as a Biomarker for Gastric Cancer Immunotherapy: A Prospective Observational Study. Issue 4 (3rd May 2020) - Xie, Tong; Liu, Yiqiang; Zhang, Zhening; Zhang, Xiaotian; Gong, Jifang; Qi, Changsong; Li, Jian; Shen, Lin; Peng, Zhi
Abstract : Immunotherapy has exhibited promising but controversial results in gastric cancer; determining criteria for choosing the appropriate target population is still problematic. Epstein-Barr virus (EBV)-associated gastric carcinoma (EBVaGC) exhibits distinctive genomic aberrations and clinicopathologic features, the positive status of EBV is a potential biomarker. We prospectively recruited 9 patients who were diagnosed with stage-IV EBVaGC, and all of the patients were treated by immune-checkpoint inhibitors. The median age of the patients was 62 years old. The clinicopathologic characteristics demonstrated a male predominance and poor differentiation status of EBVaGC. Lymph nodes were demonstrated to represent the most common metastatic site. Immunochemistry and polymerase chain reaction analysis revealed that all of the patients were proficient mismatch repair, and microsatellite instability-stable and programmed cell death-ligand 1 were detected in 7 patients. Three patients with positive programmed cell death-ligand 1 showed partial response, 5 patients showed stable disease, 1 patient without measurable lesion showed decreasing ascites and tumor marker level after immunotherapy. The longest duration of response was 18 months by the time of the last follow-up. EBVaGC exhibits distinctive clinicopathologic characteristics, and EBV-positive status may be a potential biomarker for gastric cancer immunotherapy.